Sistem Pakar Pendeteksi Penyakit Tanaman Jamur Tiram Menggunakan Metode Certainty Factor Berbasis Web - Rhido Rezwana; Dwinita Arwidiyarti; Hendri Ramdan (Jurnal PROCESSOR, 2024)
Oyster mushrooms are one of the agricultural commodities in Indonesia. Oyster mushrooms can be processed into various kinds of dishes and snacks so that the need for oyster mushrooms in society is increasing over time. Based on data from the Plantation Plantation Seed and Protection Center of West Nusa Tenggara Province, oyster mushroom production in West Nusa Tenggara Province in 2022 decreased by 28,291 kg when compared to 2021. Various disturbing factors such as pest and disease attacks, climate and errors in maintenance are the cause of decreased production. Farmers' limited knowledge in diagnosing diseases in oyster mushroom plants often results in mistakes that result in crop failure. The aim of this research is to produce an expert system that can diagnose diseases in oyster mushroom plants and provide solutions so that farmers can make prevention and treatment efforts quickly before the disease spreads to other oyster mushroom plants. This expert system was built using the Waterfall software development method. Functional testing used the Black Box Testing Method with 100% valid results, while accuracy testing was carried out using 20 cases which resulted in 19 valid cases (95% accuracy). This expert system uses the web-based Certain Factor Method so that it can be accessed by oyster mushroom farmers or anyone who needs it for free. It is hoped that this expert system can help farmers detect diseases in oyster mushroom plants and increase oyster mushroom production in the community.